THIS BOOK IS NOT GOOD FOR YOU - Bosch, Pseudonymous; Pseudonymous Bosch (United States Little, Brown Books and Company, 2009)
This Book Is Not Good for You by Pseudonymous Bosch is the third installment in The Secret Series, featuring Cass, Max-Ernest, and Yo-Yoji on a mission to rescue Cass's mother from an evil chocolatier, Señor Hugo. To save her, they must track down a legendary, dangerous tuning fork that replicates flavors. The trio navigates a thrilling, chocolate-themed adventure filled with riddles and secret societies, ultimately facing imprisonment when trying to stop the villains from utilizing the fork.
Keywords: Mystery; Adventure